Learning from the design and development of the NHS Safety Thermometer - Power, Maxine (Oxford University Press, 2014)
QUALITY ISSUE: Research indicates that 10% of patients are harmed by healthcare but data that can be used in real time to improve safety are not routinely available. INITIAL ASSESSMENT: We identified the need for a prospective safety measurement system that healthcare professionals can use to improve safety locally, regionally and nationally. CHOICE OF SOLUTION: We designed, developed and implemented a national tool, named the NHS Safety Thermometer (NHS ST) with the goal of measuring the prevalence of harm from pressure ulcers, falls, urinary tract infection in patients with catheters and venous thromboembolism on one day each month for all NHS patients. IMPLEMENTATION: The NHS ST survey instrument was developed in a learning collaborative involving 161 organizations (e.g. hospitals and other delivery organizations) using a Plan, Do, Study, Act method. EVALUATION: Testing of operational definitions, technical capability and use were conducted and feedback systems were established by site coordinators in each participating organization. During the 17-month pilot, site coordinators reported a total of 73 651 patient entries. LESSONS LEARNED: It is feasible to obtain national data through standardized reporting by site coordinators at the point of care. Some caution is required in interpreting data and work is required locally to ensure data collection systems are robust and data collectors were trained. Sampling is an important strategy to optimize efficiency and reduce the burden of measurement.